2010
DOI: 10.1088/0004-637x/715/1/429
|View full text |Cite
|
Sign up to set email alerts
|

THE FIRST CATALOG OF ACTIVE GALACTIC NUCLEI DETECTED BY THEFERMILARGE AREA TELESCOPE

Abstract: We present the first catalog of active galactic nuclei (AGN) detected by the LAT, corresponding to 11 months of data collected in scientific operation mode. The First LAT AGN Catalog (1LAC) includes 671 γ-ray sources located at high Galactic latitudes (|b| > 10 •) that are detected with a test statistic (T S) greater than 25 and associated statistically with AGNs. Some LAT sources are associated with multiple AGNs, and consequently, the catalog includes 709 AGNs, comprising 300 BL Lacertae objects (BL Lacs), 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
465
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 452 publications
(482 citation statements)
references
References 108 publications
15
465
1
1
Order By: Relevance
“…Padovani, Giommi & Rau (2012) have studied the quasi-simultaneous near-IR, optical, UV, and X-ray photometry of eleven γ-ray selected blazars, and found four high power -high synchrotron peak blazars. Ghisellini et al (2009aGhisellini et al ( , 2010, Abdo et al (2010b) and Sambruna et al (2010) have got that the correlation between γ-ray luminosity and photon index supports the blazar sequence. Chen & Bai (2011) confirmed that low power -low synchrotron peak blazars have relatively lower black hole masses.…”
Section: Introductionmentioning
confidence: 74%
“…Padovani, Giommi & Rau (2012) have studied the quasi-simultaneous near-IR, optical, UV, and X-ray photometry of eleven γ-ray selected blazars, and found four high power -high synchrotron peak blazars. Ghisellini et al (2009aGhisellini et al ( , 2010, Abdo et al (2010b) and Sambruna et al (2010) have got that the correlation between γ-ray luminosity and photon index supports the blazar sequence. Chen & Bai (2011) confirmed that low power -low synchrotron peak blazars have relatively lower black hole masses.…”
Section: Introductionmentioning
confidence: 74%
“…Our sample is composed by 229 blazars detected by Fermi/LAT 31,33 for which broad emission lines have been measured 12,13,32 . This sample does not include several bright and famous blazars with historical spectroscopic classifications in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…AGN are selected if they have been observed in γ-rays by the Fermi-LAT telescope [114] and are within a redshift of z < 0.1.…”
Section: Selected Source Limitsmentioning
confidence: 99%
“…M87 is of particular interest as the central and most massive AGN in the Virgo cluster, it is also one of the AGN associated with a Fermi-LAT γ-ray observation [114].…”
Section: Selected Source Limitsmentioning
confidence: 99%